2022
DOI: 10.1002/smll.202200784
|View full text |Cite
|
Sign up to set email alerts
|

A Versatile Electrochemical Biosensor for the Detection of Circulating MicroRNA toward Non‐Small Cell Lung Cancer Diagnosis

Abstract: Circulating microRNAs (miRNAs) can be used as noninvasive biomarkers and are also found circulating in body fluids such as blood. Dysregulated miRNA expression is associated with many diseases, including non‐small cell lung cancer (NSCLC), and the miRNA assay is helpful in cancer diagnosis, prognosis, and monitoring. In this work, a versatile electrochemical biosensing system is developed for miRNA detection by DNAzyme‐cleavage cycling amplification and hybridization chain reaction (HCR) amplification. With cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 63 publications
0
25
0
Order By: Relevance
“…Table S1 † shows the comparison of the method developed in this study and the methods currently available for the quantication of miRNA. [41][42][43][44][45][46] The method developed in this study showed an improved sensitivity with a relatively wider linear range and a lower detection limit compared to the existing methods.…”
Section: T7 Exo-powered Mirna Discriminator For Electrochemical Measu...mentioning
confidence: 99%
“…Table S1 † shows the comparison of the method developed in this study and the methods currently available for the quantication of miRNA. [41][42][43][44][45][46] The method developed in this study showed an improved sensitivity with a relatively wider linear range and a lower detection limit compared to the existing methods.…”
Section: T7 Exo-powered Mirna Discriminator For Electrochemical Measu...mentioning
confidence: 99%
“…For example, irregular expression of miRNAs and APE1 was detected in some normal cells. [27,28] As shown in Figure 1A, ATP bound its aptamer to release the blocked strand (module A), miR-141 opened the hairpin structure strand-specific endonuclease, only the activated modules A and M hybridized with high stability would LDC release signals. The ssDNA flexibility of the two modules might have a significant impact on the hybridization reaction, which in turn affected the signal output and sensitivity of LDC.…”
Section: Ldcs Design Guided By Simulationmentioning
confidence: 99%
“…The abundance of DE ncRNAs in PA has been widely reported. Investigating the roles of ncRNAs is helpful for understanding the occurrence and development of PA, and some ncRNAs can be used as biomarkers for the detection of PA [ 1 , 18 , 43 , 127 ], while other ncRNAs can contribute to the diagnosis of PA [ 52 , 85 , 90 , 112 ], distinguish the disease subtypes [ 24 , 25 , 34 , 93 ], and predict tumor invasion and progression [ 20 , 26 , 35 , 85 , 95 , 110 , 111 , 123 ]; the remaining ncRNAs may be implicated in the pathogenesis of PA [ 116 , 117 , 120 , 122 ]. In addition, the regulatory networks of lncRNA/circRNA and miRNA provide promising biomarkers for the noninvasive diagnosis and molecular therapy of PA, and exosome-derived ncRNAs bring a tremendous infusion of hope to the improvement of the disease diagnosis and future potential therapeutic targets for treatments.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%
“…Among the abundant DE ncRNAs, miRNAs are the most widely studied. We discuss the role of miRNAs in different PA subtypes in tissues, biofluids, and cell-free environments [ 17 , 18 , 19 , 20 , 37 ]. miRNAs inhibit the expression of target genes at the post-transcriptional level by pairing with the 3′-UTR of mRNA ( Figure 1 ); thus, miRNAs are involved in various pathological and physiological processes by playing a negative role in cell proliferation, differentiation, metabolism, and apoptosis.…”
Section: Conclusion and Future Perspectivementioning
confidence: 99%